GAMBARAN PENGGUNAAN ANTIBIOTIK TERHADAP PENGETAHUAN JEMAAT GMIM SION MADIDIR URE - Tempo, Cornelia Helena; Moleong, Maxie M. L.; Toar, Jilly (Yayasan Syalom Cipta Sumikolah, 2024)
Background: Antibiotics are drugs that are widely used to treat infections caused by bacteria. Prescription of antibiotics is often given in the treatment of patients, but inappropriate use can trigger resistance in bacteria. The lack of knowledge about appropriate antibiotics by the public is the main point of resistance. From the results of initial observations carried out at the GMIM Sion Madidir Ure Congregation, interviews showed that 10 out of 15 respondents had poor knowledge of the use of antibiotics and 5 of them only had good knowledge. Objective: To find out the description of the use of antibiotics on the knowledge of the GMIM Sion Madidir Ure congregation. Methodology: The research used was a descriptive analytical research method with a survey approach carried out during June 2024. The population in this research was the entire GMIM Sion Madidir Ure congregation, totaling 262 people making up 70 samples with a sampling technique using purposive sampling technique. The research was carried out by observing the variable knowledge of antibiotic use in the GMIM Sion Madidir Ure congregation. Data analysis was carried out univariately. Results: The research results show that the majority of respondents who answered had little knowledge were 40 people (57.14%) and those who answered had good knowledge were 30 people (42.85%).